Design and modelling of generator for wave energy conversion system in Malaysia - Zamri, N.A.M. (UK Simulation Society, 2017)
This paper presents the design and modelling of generator for wave energy conversion system in Malaysia. This paper aims to identify the most promising topology to be used and to propose initial designs of the generator. Literature review on the previous technologies, power take-offs and linear generator have been completed and from the review, the criteria for the proposed generator designs are acquired. Two designs have been proposed in which one of the designs utilizes alternate slot winding concept. Both of the designs are simulated using Finite Element software, Ansys Maxwell. The preliminary results of flux distribution, air gap flux density, flux linkage and induced back EMF are obtained. From the simulation results, air gap flux density of both designs is within the expected range. It is also found that by implementing alternate slot winding concept, even though the total number of turn is the same, the induced back EMF produces is slightly lower than the full slot winding. © 2017, UK Simulation Society. All rights reserved.